Epidemiological characteristics of brucellosis in Vojvodina, Serbia, 2000–2014 - Štrbac, Mirjana; Ristić, Mioljub; Petrović, Vladimir; Savić, Sara; Ilić, Svetlana; Medić, Snežana; Radosavljević, Biljana; Vidić, Branka; Grgić, Živoslav (Vojnosanitetski pregled, 2018)
Background/Aim. Despite the fact that brucellosis occurs sporadically in the epidemic form, this disease is still one of the world’s most widespread zoonoses. Methods. Data from the register of infectious diseases of the Institute of Public Health of Vojvodina and Scientific Veterinary Institute in Novi Sad were used in this study. Using descriptive statistics, data were analyzed for the period 2000 to 2014. Results. In the observed period in Vojvodina 102 cases of brucellosis were registered with different frequency of notification cases by districts of province. Most frequent modes of transmission of brucellosis were consumption of contaminated food (especially sheep cheese) or direct contact with domestic animals. In 70.2% of the patients, occupational exposures to the agent or direct daily contact with animals were noted. The dominant source of infection in the urban area was food, whereas a direct contact with sick animals was dominant mode of transmission in the rural area. Overall, 14 epidemic outbreaks of brucella were registered with direct contact as dominant mode of transmission. The predominant age-range of patients with brucella confirmed infections was 30–59 years (50.0 male %), and 2.5 times more males than females were affected. Seasonal distribution was highest during spring, with 50.0% of all confirmed cases. During the period 2004–2005, prevalence of serum positive patients in the South Bačka District coincided with the highest number of laboratory confirmed serum samples among animals. Conclusion. Although the incidence of brucellosis shows a declining trend, education and improving of surveillance of disease of all relevant institutions seems as necessary for better recognition and notification of the disease.